Direct molecular identification of Trypanosoma cruzi discrete typing units in domestic and peridomestic Triatoma infestans and Triatoma sordida from the Argentine Chaco - Maffey, L (2012)
Fil: Maffey, L. Universidad de Buenos Aires. Departamento de Ecología. Laboratorio de Eco-Epidemiología, Genética y Evolución; Argentina.